OPTICAL-GRAPHICAL DISORDERS IN THE WRITING OF VISUAL IMPAIRED PRIMARY SCHOOLERS (EDUCATION IN THE 21ST CENTURY, 2023)
This article reviews the main optical-graphical disorders of writing in visually impairedprimary schoolers. It is known, that visual impairment significantly complicates the playing,physical, cognitive, educational, labour and other types of activities of children, their orientation inmacro and micro spaces. Therefore, the role of vision in writing can hardly be overestimated.The visual control plays a very important role in observing graphical norms, rules andconditions of writing in the formation and development of visual skills of visually impaired140students. In this connection, the study of optical-graphical disorders in the writing of visuallyimpaired primary schoolers will serve the basis for the development of special pedagogicalapproaches and terms of application for the organization and implementation of work aimed at theprevention and correction of graphical writing disorders of visually impaired primary schoolers.It is well known, that the formation and development of graphical skills of visually impairedstudents is to be started from the first grade, as it is more difficult to correct or eliminate opticalgraphicalwriting disorders in higher grades. Thus, the success of all the work depends on theinformative level of primary school's teachers about graphical writing disorders of their students,the means, methods and conditions of their use for carrying out the prevention and correctionworks. This defines the necessity to study optical-graphical writing disorders of visually impairedprimary schoolers and to develop special pedagogical approaches and conditions for theprevention and correction of these disorders.
Keywords: visually impaired child, primary school students, op- tic-graphic writing disorders, prevention, correction, teacher, viewer new perception, means, methods, pedagogical approaches